Peranan LPD Desa Pakraman Sesetan Terhadap Masyarakat Desa Sesetan - WAHYU DUCARO SEMBIRING; I WAYAN GINARSA; I KETUT RANTAU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2013)
ABSTRACT Role of LPD Sesetan for Villagers Sesetan The purpose of this study is determine the role of LPD Sesetan seen from fund raising activities of society (savings, deposits and loans) and the efforts made by the LPD Sesetan that people feel the presence of LPD is important seen from LPD counseling to the community. The study location was chosen with consideration LPD Sesetan was formed with the aim of encourage the economic development of rural communities (eradicate bonded labor among farmers) through savings and capital distribution of effective and LPD Sesetan have a complete accounting. The development of unit operations is also quite good even increased every years and members continues to increase every years. Advice that can be given to the LPD in order to seek a better way to attract people Village People Sesetan to become members of the LPD. Keyword: communities, role, bonded